Recent Advances in Understanding the Role of Growth Regulators in Plant Growth and Development in vitro - III. Inhibitors of Growth Regulators - Singh, Rohtas; Kumar, Suresh; Kalia, Sanjay; Sharma, S. K.; Kalia, Rajwant K. (Indian Forester, 2016)
Discovery of plant growth regulators have materialized Haberlandt's concept of totipotency coined more than a century ago. A number of tissue culture based biotechniques are now possible due to the ability of growth regulators to influence morphogenesis. Physiological functions of most of the classical PGRs have been studied for decades, however, discovery of chemicals that interfere with synthesis, transport and action of endogenous growth regulators have further improved our knowledge regarding the role of these plant growth regulators in plant's growth and development. This review summarizes the role of such interfering and inhibiting compounds in in vitro growth and development of plants.